A COMPARATIVE STUDY OF THE NATURE AND SEVERITY OF FOOT INJURIES IN MALE ATHLETES PLAYING TEAM AND INDIVIDUAL SPORTS AT UNIVERSITY LEVEL - Choudhari, Shishir Diliprao; Charade, Anil Purushottam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sports and physical activity are an integral part of human life, which enhance physical fitness, mental well-being and social interaction. However, participation in sports also carries the risk of injuries, especially to the lower body, which includes the waist, hips, knees, ankles and feet. Lower body injuries are the most common and debilitating for athletes, often leading to prolonged recovery periods, reduced performance and, in severe cases, the end of a sporting career. Although injuries are a universal concern for athletes, the nature and frequency of these injuries can vary significantly between individual and team sports. Comparative studies of lower body injuries sustained by athletes involved in individual and team sports are of great importance for several reasons, including injury prevention, performance enhancement, and the advancement of sports science.